"I Didn't Expect to Be So Caught Up in It": a Qualitative Study of Experiences of Medical Students' Volunteering for Ukrainian Refugees - Motlová, Lucie Bankovská; Vlčková, Karolína; Prokešová, Barbora; Suchánková, Eliška; Štirská, Lucie; Janoušková, Miroslava (Academic psychiatry, 2023)
OBJECTIVE: Russia's invasion of Ukraine in February 2022 triggered a huge wave of migration, with thousands of refugees arriving at Prague's Central Station. With no medical service available, medical students started to volunteer and were running an infirmary available around the clock. The research aimed to explore medical students' professional experiences, emotionally challenging situations, and coping strategies in this demanding setting. METHODS: The authors used a qualitative analysis of semi-structured in-depth interviews with 19 participants recruited through purposive sampling. Interviews took place between April and May 2022. Data were recorded, transcribed, and processed by using thematic qualitative analysis. RESULTS: The research identified five emotionally challenging situations: caring for traumatized refugees, refusal of treatment, disruption of everyday life, independent decision-making, and complexity of voluntary work. Students adopted both adaptive and maladaptive coping strategies for dealing with stress and trauma. Almost half the students reported signs of secondary traumatization and moral distress; however, no one asked for psychological help. CONCLUSIONS: Medical school curricula should cover trauma-informed approaches, healthy coping strategies, and destigmatization of psychological problems.
Keywords: dobrovolní pracovníci; Forced migration; Refugees; lidé; studenti lékařství; Secondary trauma; kvalitativní výzkum; Qualitative Research; kurikulum; Humans; Volunteering; Coping strategies; Medical students; Students, Medical; uprchlíci; Health Status; Curriculum; zdravotní stav; Volunteers